Investment liberalisation, technology take-off and export market entry: does foreign ownership structure matter? - Girma, Sourafel; Gong, Yundan; Görg, Holger; Lancheros, Sandra (Elsevier, 2015)
In the run up to its accession to the WTO in 2001, China has undergone far-reaching investment liberalisation. As part of this investment liberalisation process, existing restrictions on foreign ownership structure and mandatory export and technology transfer requirements imposed on foreign firms have been lifted in a number of industries. We exploit these facts to identify the causal effects of foreign acquisitions on export markets entry and technology take-off and to evaluate whether the level of foreign ownership plays a role in stimulating these changes. Using doubly robust propensity score reweighted bivariate probit regressions to control for the selection bias associated with firm level foreign acquisition incidences, we uncover strong but heterogeneous positive effects on export activity for all types of foreign ownership structure. We also find that minority foreign owned acquisition targets experience higher likelihood of R&D, providing evidence that joint ventures between foreign owners and Chinese firms can contribute positively to China’s “science and technology take-off”.